High consumption of fatty fish from the Baltic Sea is associated with changes in human lymphocyte subset levels - Hagmar, Lars; Hallberg, Torgny; Leja, Marcis; Nilsson, Anita; Schütz, Andrejs (Toxicology letters, 1995)
Fatty fish from the Baltic Sea accumulate immunotoxic persistent organochlorine compounds. In a previous study we found inverse correlations between such fish consumption and natural killer (NK) cell levels in a Swedish population. The present study concerns 68 Latvian subjects with high, low or intermediate fish consumption. High fish consumption correlated positively with B cell levels and CD4+/CD8+ ratios, but negatively with levels of cytotoxic (CD8+) T cells. Furthermore, NK cell levels correlated inversely with plasma selenium, one of several strong correlates with fish intake. A high fish diet includes a set of possible immunomodulating agents. It is presently not possible to pinpoint the cause for the observed subset deviations or to establish their possible biological importance.